1980-1981 Basketball Pictures #47 - Missouri Southern State University (1981)
Jerry Wilson (#44), PAGE NO. #91, PIX NO. #1; Do you recognize a person in the photograph, or know the place or event where the photograph was taken? Tell us about it!